EFFORTS TO IMPROVE STUDENT LEARNING OUTCOMES BY APPLYING THE STAD-TYPE COOPERATIVE LEARNING MODEL - Jonni Mardizal; Muhammad Tarmizi (Jurnal Inovasi Penelitian, 2021)
This study is a study that applies the STAD (Student Teams Achievement Division) cooperative learning model to improve student learning outcomes in Construction Cost Estimation subjects. The method used in this study is classroom action research (CAR). Research takes the form of cycles that last twice the cycle, depending on the success rate of the target achieved. The research subject in this study was a student of class XI Design Modeling and Building Information (DPIB) Vocational High School (SMK) Negeri 5 Sungaipenuh. The number of students in this class is 14 students. Data analysis techniques are carried out by assessing the activeness of students' learning and assessment of learning outcomes. Student learning outcomes in the first cycle with a total of 14 students, with an average score of 72.86, and students who achieved the completion of 8 people's learning, which is 57.14%. In the second cycle with the number of students was 14 people, with an average score of 79.29, and students who achieved the completion of learning 11 people, namely 78.57%. In this second cycle, the average grade of students has reached above the Minimum Completion Criteria (MCC).